2016
DOI: 10.1002/cpt.521
|View full text |Cite
|
Sign up to set email alerts
|

Essential competencies in prescribing: A first european cross‐sectional study among 895 final‐year medical students

Abstract: European medical students should have acquired adequate prescribing competencies before graduation, but it is not known whether this is the case. In this international multicenter study, we evaluated the essential knowledge, skills, and attitudes in clinical pharmacology and therapeutics (CPT) of final‐year medical students across Europe. In a cross‐sectional design, 26 medical schools from 17 European countries were asked to administer a standardized assessment and questionnaire to 50 final‐year students. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 26 publications
4
91
2
9
Order By: Relevance
“…Curriculum designers tend to place more emphasis on diagnostic rather than therapeutic reasoning, with the former being perceived as more challenging and difficult 14. Consistent with the views of final‐year students in Europe,6 CPT education was mainly based on traditional learning methods such as lectures and written examinations, rather than on context‐based learning methods, such as patient simulation and workplace assessments. In fact, a large proportion (39%) of schools used solely traditional learning methods, which could in part explain why respondents indicated that students were not well prepared for rational prescribing.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Curriculum designers tend to place more emphasis on diagnostic rather than therapeutic reasoning, with the former being perceived as more challenging and difficult 14. Consistent with the views of final‐year students in Europe,6 CPT education was mainly based on traditional learning methods such as lectures and written examinations, rather than on context‐based learning methods, such as patient simulation and workplace assessments. In fact, a large proportion (39%) of schools used solely traditional learning methods, which could in part explain why respondents indicated that students were not well prepared for rational prescribing.…”
Section: Discussionmentioning
confidence: 90%
“…Rational prescribing is a complex skill that requires various high‐level cognitive processes,16 and thus attending lectures and passing written examinations probably do not prepare students sufficiently for this task. A recent study showed that students taught with mainly traditional learning curricula have significantly weaker prescribing competencies than students taught with mainly problem‐based learning curricula 6. The WHO Guide to Good Prescribing model has been shown to be the only effective method to teach rational prescribing in a wide variety of international settings,17, 18, 19 yet fewer than 20% of the respondents used this model in their teaching program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of CPT topics, most articles (32%) evaluated competencies in antimicrobial prescribing and resistance, and in general prescribing (26%). Most studies (85%) used a cross‐sectional survey as the primary evaluation method; other evaluation methods comprised clinical cases ( n = 3) 10, 21, 22, clinical vignettes ( n = 3) 23, 24, 25, multiple‐choice exams ( n = 2) 10, 26, therapeutic consultations with patients in general practice ( n = 1) 27, drug prescriptions during internship ( n = 1) 28 and a mixture of quantitative and qualitative methods ( n = 1) 29. In total, 10 339 final‐year medical students were involved.…”
Section: Resultsmentioning
confidence: 99%
“…knowledge, skills and attitudes) among junior doctors is frequently mentioned 7, 9, which might be due to inadequate undergraduate education and training in clinical pharmacology and therapeutics (CPT). Indeed, a recent study showed that European final‐year medical students lacked essential prescribing competencies and felt that their medical curriculum had not adequately prepared them for safe prescribing 10. Another recent study showed that CPT education across Europe is still mainly based on traditional learning methods (e.g.…”
Section: Introductionmentioning
confidence: 99%